2020
DOI: 10.1089/sur.2019.199
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors and Microbial Spectrum for Infectious Complications after Hepatectomy with Cholangiojejunostomy in Perihilar Cholangiocarcinoma

Abstract: Background: Despite advances in surgical techniques and peri-operative management, post-operative infectious complications still are common after perihilar cholangiocarcinoma (PHCC). This study investigated the predictive factors and microbial spectrum for infections after hepatectomy with cholangiojejunostomy performed to treat PHCC. Methods: A total of 70 consecutive patients, who underwent hepatectomy with cholangiojejunostomy by the same surgeons at a tertiary referral medical center between September 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The occurrence of postoperative complications is also one of the factors influencing serum TC level. After retrospectively analyzing 70 patients with hilar cholangiocarcinoma, Chen et al found that hypocholesterolemia on the first postoperative day was an independent risk factor for postoperative infectious complications [ 36 ]. Nuzzo et al reported that postoperative serum TC level under 1.3–1.5 mmol/L often indicates the occurrence of postoperative sepsis after hepatopancreatobiliary surgery, and persistent hypocholesterolemia hints at more severe disease condition and worse prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of postoperative complications is also one of the factors influencing serum TC level. After retrospectively analyzing 70 patients with hilar cholangiocarcinoma, Chen et al found that hypocholesterolemia on the first postoperative day was an independent risk factor for postoperative infectious complications [ 36 ]. Nuzzo et al reported that postoperative serum TC level under 1.3–1.5 mmol/L often indicates the occurrence of postoperative sepsis after hepatopancreatobiliary surgery, and persistent hypocholesterolemia hints at more severe disease condition and worse prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Hypernatremia may be associated with increased risk for infection due to cellular dehydration, which may cause immune and metabolic dysregulation, allowing microorganisms to thrive. 21,23 Furthermore, elevated serum bilirubin was a predictor for increased postoperative morbidity and mortality after hepatectomy. 24 Patients with higher bilirubin also had significantly higher intraoperative blood loss, blood transfusion, and blood replacement.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%